Parental Social Support and Moral Intelligence in Junior High Students: Dukungan Sosial Orang Tua dan Kecerdasan Moral pada Siswa SMP - Ramadhan, Linda; Affandi, Ghozali Rusyid (Psikologia : Jurnal Psikologi, 2025)
The purpose of this study is to identify the correlation between parental social support and moral intelligence at SMP X in Sidoarjo. This study uses a correlational type of quantitative research using parental social support variables as independent variables and moral intelligence variables as dependent variables. This study was conducted on students of SMP X in Sidoarjo with a population of 167 students so that the slovin formula of the population to 118 students was used as a research sample using the non-probobility sampling technique of accidental sampling method. The data collection technique used a parental social support scale and a moral intelligence scale in the form of a Likert scale. The hypothesis in this study is whether there is a relationship between parental social support and moral intelligence in SMP X students in Sidoarjo. Data analysis was carried out using product moment correlation techniques using SPSS software version 23. The results of the data analysis showed a correlation coefficient value of 0.303 with a significance level (0.001<0.05), this shows that the hypothesis is accepted which means that the two variables have a positive relationship Highlights: Positive Correlation – The study found a significant positive relationship between parental social support and students' moral intelligence (r = 0.303, p < 0.05). Influential Factors – Parental support includes emotional, informational, and instrumental aspects, which contribute to students' moral behavior and decision-making. Developmental Impact – Strong parental involvement helps students navigate adolescence with higher moral awareness, reducing negative behaviors like delinquency. Keyword: Parental Social Support, Moral Intelligence, Adolescence, Education, Psychological Development